Classical relativistic spin particles - Llosa, J. (Condensed Matter Physics, 1998)
Relativistic spin particles are approached from the stand point of Hamiltonian actions of Poincare group on itself. The several possible solutions are classified and realizations are given in terms of Dirac’s constraints formalism.